Public willingness to pay watershed eco-compensation in China’s Taihu basin: A case study - Deng, Menghua; Li, Zhiqi; Chen, Junfei; Tao, Feifei (Frontiers in Environmental Science, 2022)
Eco-compensation is effective in promoting the sustainable development of watershed. The exploration of the public's willingness to pay for eco-compensation and the corresponding influencing factors are important to improve the efficiency and efficacy of eco-compensation programs. However, how to motivate the public to participate in eco-compensation is still a challenge. In this study, the willingness and the influencing factors of public participate in eco-compensation are measured by the contingent valuation method and random forest model. The main results show that (1) the mean willingness to pay for eco-compensation is 287.344 CNY/person/year in the Taihu Basin. (2) The importance of watershed ecological environment protection, the impact of watershed ecological environment on lives, annual income, and the improvement of the watershed ecological environment in the recent five years are the significant influential factors. (3) The awareness of ecological environment protection can promote the public to pay for eco-compensation. This study can provide references for the governments to formulate and implement the eco-compensation policy and promote public participation in eco-compensation.